Catalyst-Free Hydrogenation of Alkenes and Alkynes with Hydrazine in the Presence of Oxygen - Menges, Nurettin; Balci, Metin (Synlett, 2014)
A series of alkenes and alkynes was subjected to reduction with hydrazine hydrate in ethanol in the presence of oxygen. An efficient method was developed for the reduction of C–C double bonds and C–C triple bonds with diimide, generated in situ from hydrazine hydrate by oxidation with oxygen. The reduction process proceeded for 24–48 hours with high chemoselectivity and excellent yields. This reduction procedure offers synthetic advantages over metal-catalyzed hydrogenation as well as other systems.
Keywords: reduction; oxidation; hydrazine; hydrogenation; diimide